Sponsorship in context - Waite, Nigel (Cranfield University, 1979)
The research described in this thesis is aimed at initiating a factually-based knowledge of the sponsorship of leisure pursuits as a promotional tool. Research to date has been scant leaving the subject largely in the realms of supposition. The finding of this research can be classified under three headings: 1A description of the overall sponsorship process 2 The evaluation of sponsorship 3 The implications for marketing management in general. Based upon the first phase of field research the author constructs an overview of the sponsorship process. This demonstrates the wide range of industries which engage in sponsorship, identifies decision-making factors, sponsor- ship effects, and evaluation. Sponsorship is seen to be employed mainly in a strategic role, in that it is used to contribute to long term objectives. Marked disparities are observed between the effects claimed for sponsorship and the incidence of those claims being supported by evaluation. In the second phase of research the evaluation methods adopted by sponsors are thoroughly investigated. It is observed that sponsorship objectives are generally too vague for worthwhile evaluation to be possible. More- over, available information is not used properly as an input to improved practice. It is perceived that sponsorship can have a much more powerful role to play than is commonly understood. As a new means of promotion, sponsorship can imbue a brand or company with the part- icular characteristics which the relevant sport or art possess. It provides an additional' vehicle for communic- ation and is a novel means for targeting particular groups of people. Thirdly, are the impications of the research for marketing management in general. From the literature review it is argued that there should be a direct relation- ship between decision-making and evaluation. Evaluation is the link which feeds information about the results of decisions back into better subsequent decision-making; and central to this process are well-defined objectives. The failure by managers to fully appreciate and practice this process is underlined.